2013
DOI: 10.2118/134464-pa
|View full text |Cite
|
Sign up to set email alerts
|

Sand Prediction: A Practical Finite-Element 3D Approach for Real Field Applications

Abstract: Summary Sand production is a critical issue in the oil and gas industry. During the production of a well, sand production may have negative consequences, such as risk of well failure, erosion of pipelines and surface facilities, and the need for sand separation and disposal. Knowing the conditions for the onset of sand production allows optimizing sand free production and, eventually, avoiding or delaying the use of sand-control methods. The aim of this work is to establish a reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The numerical simulation method studies the coupled situation of fluid and solid phases in the formation. Volonté established a dynamically coupled numerical model of rock and fluid mechanics [3]. The model parameters are complicated and difficult to obtain, and the calculation process is time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulation method studies the coupled situation of fluid and solid phases in the formation. Volonté established a dynamically coupled numerical model of rock and fluid mechanics [3]. The model parameters are complicated and difficult to obtain, and the calculation process is time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…They found the fracture mechanism was a combination of volume collapse (compaction zone formation) and hydrodynamic transport of failed material, and the sand production volume monotonically increased with simulation time. Volonté et al 31 established a three‐dimensional (3D) coupled model using finite element modeling to simulate fluid flow and rock deformation, and quantified the spatial distribution and damage severity of the rock around the perforation, adopting several optimal geometries and meshes describing the wellbore, perforation tunnel, and surrounding strata. Kim et al 32 showed a 3D numerical model quantitatively describing the sand failure, erosion, and production.…”
Section: Introductionmentioning
confidence: 99%
“…In general, sand production is investigated with models based on field or experimental observations often calibrated by field or laboratory data to prove their predictive efficiency. Research works on numerical, analytical and experimental investigations include: Qiu et al, 1 Osisanya, 2 Papamichos, 3 Rahmati et al, 4 Volonte et al, 5 Ikporo and Sylvester, 6 Wang and Sharma, 7 Gravanis et al, 8,9 Gholami et al, 10 Li et al, 11 Eshiet et al, 12 Fetrati and Pak, 13 van den Hoek et al, 14 Subbiah et al, 15 Sarris et al, 16 Ma et al, 17 Zhang et al 18 and Kakonitis et al 19 Many researchers have attempted to explain the cause of sand production. Sanding is attributed to the increase of effective Rate of softening (Eqs.…”
Section: Introductionmentioning
confidence: 99%